2022
DOI: 10.1371/journal.pone.0274581
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral transitional vertebrae alter the distribution of lumbar mobility–Preliminary results of a radiographic evaluation

Abstract: Background Lumbo-sacral transitional vertebrae (LSTV) are one of the most common congenital variances of the spine. They are associated with an increased frequency of degeneration in the cranial adjacent segment. Hypermobility and concomitant increased loads are discussed as a possible reason for segmental degeneration. We therefore examined the lumbar and segmental motion distribution in patients with LSTV with flexion-extension radiographs. Methods A retrospective study of 51 patients with osteochondrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Please notice dramatic pain reduction after surgery. Variable VAS scores P-Value 1 G1 G2 Median (IQR) Median (IQR) Radicular Pain Before 9 8 , 9 9 8 , 9 0.204 One month later 7 6 , 7 6 6 , 7 , 8 0.015 Three months later 5 4 , 5 , 6 4 3 , 4 , 5 , 6 <0.001 Six months later 3 2 , 3 , 4 , 5 2 2 , 3 , 4 , 5 <0.001 P-Value 2 0.002 0.001 Back Pain Before 8 7 , 8 , 9 8 7 , 8 0.870 One month later 8...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please notice dramatic pain reduction after surgery. Variable VAS scores P-Value 1 G1 G2 Median (IQR) Median (IQR) Radicular Pain Before 9 8 , 9 9 8 , 9 0.204 One month later 7 6 , 7 6 6 , 7 , 8 0.015 Three months later 5 4 , 5 , 6 4 3 , 4 , 5 , 6 <0.001 Six months later 3 2 , 3 , 4 , 5 2 2 , 3 , 4 , 5 <0.001 P-Value 2 0.002 0.001 Back Pain Before 8 7 , 8 , 9 8 7 , 8 0.870 One month later 8...…”
Section: Resultsmentioning
confidence: 99%
“… 3 Recent studies found that lumbar sacralization increases the chance of developing LBP, the severity, and the probability of lumbar disc herniation. 4 , 5 , 6 However, the role of lumbar sacralization in the development and outcome of LBP and disc degeneration is questioned by other studies. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%